The Isolation and Identification of Thiamine-Binding Protein from Black Glutinous Rice Bran (Oryza Sativa var. Glutinosa) - Gunarti, Dwirini; Josua Kristinao Hilmanto (EKSAKTA: Journal of Sciences and Data Analysis, 2024)
Thiamine is a crucial cofactor in energy metabolism. Deficiency of this vitamin can cause disorders in the nervous and cardiovascular systems. Conventional methods for examining thiamine levels in the body are expensive. One solution is using a technique similar to ELISA, namely ELPLA, which uses thiamine-binding protein as an antibody substitute. This study aims to investigate the presence of thiamine-binding protein in black glutinous rice bran (Oryza Sativa var. Glutinosa). The methods used include salting out, dialysis, and equilibrium dialysis. The results show the presence of thiamine-binding protein in black glutinous rice bran, evidenced by equilibrium dialysis.